Parametric design method and performance analysis of double S-shaped nozzles - Shan, Yong (2020)
A parametric design method, which was based on super-elliptical transition and self-adaption infrared radiation shield for the double S-shaped nozzle, was introduced. The complete shielding of high-temperature components in the S-shaped nozzle was realized. Model experiments and numerical simulations were performed to investigate the effects of offset ratio S/D, the ratio of length to diameter L/D, and the aspect ratio W/H on the aerodynamics and infrared radiation. The results showed that the total pressure recovery and thrust coefficients were improved initially, but dropped rapidly with the increase in offset ratios with the range of investigated parameters. There existed an optimal offset ratio for the aerodynamic performances. Considering the weight penalty, the length of nozzles should only be increased properly to achieve better aerodynamic performances. Both friction and viscous losses caused by large streamwise vortices dominated the aerodynamic performances of nozzles. The nozzle with the aspect ratio of W/H = 5 0 was recommended for achieving optimal aerodynamics. The increase in aspect and offset ratios could effectively suppress plume radiation, which was, however, not sensitive to overall radiation. Compared to circular nozzles, double S-shaped nozzles reduced overall infrared radiation by over 50%, which proves significant stealth ability. A balance between aerodynamic performances and infrared radiation suppression could be reached for double S-shaped nozzles.